Multiply.
5x2 - 6x +2
X
4x2 - 3x

O A. 20x4 - 39x3 + 18x2 - 6x
B. 20x4 - 24x3 + 26x2 - 6x
O C. 20x4 - 24x3 + 18x2 - 6x
O D. 20x4 - 39x3 + 26x2 - 6x

Respuesta :

Answer:

answer D

Step-by-step explanation:

hello,

[tex](5x^2-6x+2)(4x^2-3x)=4x^2(5x^2-6x+2)-3x(5x^2-6x+2)\\20x^4-24x^3+8x^2-15x^3+18x^2-6x\\=20x^4-39x^3+26x^2-6x[/tex]

hope this helps

Answer:

20x^4 - 39x^3 + 26x^2 - 6x

Step-by-step explanation:

Multiply every term of the first polynomial by every term of the second polynomial. then collect like terms.

(5x^2 - 6x +2) * (4x^2 - 3x) =

= 20x^4 - 15x^3 - 24x^3 + 18x^2 + 8x^2 - 6x

= 20x^4 - 39x^3 + 26x^2 - 6x